2023
DOI: 10.31219/osf.io/5w3dg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond persuasion: Improving conversational quality around high-stakes interpersonal disagreements

Abstract: Heated discourse over controversial topics can harm relationships while failing to change minds. In four pre-registered experiments (N = 3,707) we tested a brief intervention to mitigate the interpersonal costs of disagreement and increase the likelihood of future conversations around vaccine hesitancy. Specifically, we randomly assigned vaccine-supportive participants to training in signaling receptiveness to a vaccine-hesitant person's views. Across three studies, participants who were trained to signal rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recent research on conversational receptiveness with vaccine-hesitant people suggests that this strategy could be effective in addressing conspiracy beliefs. In five pre-registered studies, Minson et al (2023) found that vaccine-supportive people trained in conversational receptiveness were perceived as more reasonable and trustworthy when responding to vaccine-hesitant people's messages about vaccines, compared to those who were asked to respond to these messages without such training (they were simply asked to be as persuasive as they could). Furthermore, vaccine hesitant people were more willing to talk about vaccines with someone trained in conversational receptiveness (Minson et al 2023).…”
Section: Being Receptivementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on conversational receptiveness with vaccine-hesitant people suggests that this strategy could be effective in addressing conspiracy beliefs. In five pre-registered studies, Minson et al (2023) found that vaccine-supportive people trained in conversational receptiveness were perceived as more reasonable and trustworthy when responding to vaccine-hesitant people's messages about vaccines, compared to those who were asked to respond to these messages without such training (they were simply asked to be as persuasive as they could). Furthermore, vaccine hesitant people were more willing to talk about vaccines with someone trained in conversational receptiveness (Minson et al 2023).…”
Section: Being Receptivementioning
confidence: 99%
“…In five pre-registered studies, Minson et al (2023) found that vaccine-supportive people trained in conversational receptiveness were perceived as more reasonable and trustworthy when responding to vaccine-hesitant people's messages about vaccines, compared to those who were asked to respond to these messages without such training (they were simply asked to be as persuasive as they could). Furthermore, vaccine hesitant people were more willing to talk about vaccines with someone trained in conversational receptiveness (Minson et al 2023). Receptiveness fosters a sense of personal integrity and adequacy, which are important components of self-affirmation that are known to neutralise the interpersonal effects of ostracism on conspiracy beliefs (see Poon et al 2020).…”
Section: Being Receptivementioning
confidence: 99%
“…As mentioned above, another common approach to studying conflict experimentally is to recruit opposing partisans from ongoing real-world conflict for live interaction. Researchers then commonly manipulate the participants' instructions for how they ought to behave during the engagement (Jeong, Minson, Yeomans, & Gino, 2019;Minson et al, 2023;Schroeder, Risen, Gino, & Norton, 2019;Yeomans et al, 2020), the information they have about each other or their discussion topic (Santos et al, 2022), their goals for the task (Collins et al, 2022), or the manner in which people communicate (Schroeder et al, 2017). While logistically challenging, this approach can lead to rich data augmenting the traditional survey responses ranging from recordings of natural language discussions, to video, to eye-tracking and biological data.…”
Section: Interactive Experiments Engaging Participants In Ongoing Con...mentioning
confidence: 99%
“…Although this approach often focuses on synchronous interaction, creative use of technology also enables asynchronous engagement. For example, rather than trying to pair participants to interact in real time, some studies have required participants to respond to previously crafted messages from opponents, often extending the process for several rounds of message exchange over days or weeks (Yeomans et al, 2020;Minson et al, 2023).…”
Section: Interactive Experiments Engaging Participants In Ongoing Con...mentioning
confidence: 99%
“…On top of tailoring, refuting health misinformation in an empathetic way may be judged as more reliable and satisfying than refuting it HOLFORD, SCHMID, FASCE, AND LEWANDOWSKY directly and factually (Gesser-Edelsburg et al, 2018). To achieve this, refutations can use language that includes features such as acknowledgment, first-person pronouns, and use of modal conditionals, which is perceived as more empathetic than language without these features (Minson et al, 2023). For instance, "I see your point.…”
mentioning
confidence: 99%